2014
DOI: 10.1016/j.proche.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect A Glycosidic Flavonol Isolated from Green Grass Jelly (Cyclea Barbata Miers) Leaves

Abstract: A flavonoid was isolated from aqueous fraction of green grass jelly (Cyclea barbata Miers) leaf extract. On the basis of paper as well as thin layer chromatographic pattern, acid hydrolysis, and ultraviolet-visible spectrophotometric analysis, the isolate was confirmed as a 3-O-glycosidic flavonol with a hydroxyl group at C-4' and an o-di OH of A ring at position of either 6,7 or 7,8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
9
0
2
Order By: Relevance
“…revealed that flavonoids contained in the leaves of green grass jelly are a flavonol 3-oglikosida [17]. A previous study by Chen et al revealed that flavonoids in Lonicera japonica could reduce pro-inflammatory cytokines in the wound excision in day 1 and 9 post-creation of the wound [32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…revealed that flavonoids contained in the leaves of green grass jelly are a flavonol 3-oglikosida [17]. A previous study by Chen et al revealed that flavonoids in Lonicera japonica could reduce pro-inflammatory cytokines in the wound excision in day 1 and 9 post-creation of the wound [32].…”
Section: Discussionmentioning
confidence: 98%
“…This plant is easily cultivated and grows wild [16]. Substances contained in the Cincau are alkaloids, flavonoids, and polysaccharide pectin [15][16][17][18][19]. Alkaloids and flavonoids are antioxidants compounds that function as an immune stimulant to macrophages and scavenger of the free radicals in burns [18,19].…”
Section: Dewi Et Almentioning
confidence: 99%
“…One herb that has been shown empirically to have anti-inflammatory properties is Cyclea barbata Miers. C. barbata leaves are often used to treat diarrhea, abdominal pain, fever, inflammation, hypertension, and oral ulceration [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, grass jelly is known as a traditional functional drink which has specific health benefit [1], [2]. Both Cyclea Barbata Miers and Mesona Palustris Bl, varieties of grass jelly, were commonly used as raw material to make grass jelly [3], [4]. Fig.…”
Section: Introductionmentioning
confidence: 99%